2015
DOI: 10.1111/ejn.13079
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin enhances the phosphorylation of epidermal growth factor receptor and fibroblast growth factor receptor in the subventricular zone and promotes the proliferation of neural precursor cells and oligodendrocyte differentiation

Abstract: Phenytoin is a widely used antiepileptic drug that induces cell proliferation in several tissues, such as heart, bone, skin, oral mucosa and neural precursors. Some of these effects are mediated via fibroblast growth factor receptor (FGFR) and epidermal growth factor receptor (EGFR). These receptors are strongly expressed in the adult ventricular-subventricular zone (V-SVZ), the main neurogenic niche in the adult brain. The aim of this study was to determine the cell lineage and cell fate of V-SVZ neural proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This role in stem cell differentiation appears to be widespread among bilaterian animals (Freeman et al, 1992;Galvez-Contreras et al, 2015;Yoo et al, 2004). Moreover, studies performed in Drosophila and mouse have demonstrated the role of the EGFR pathway in the maintenance of the intestine (Jiang et al, 2011;Wong et al, 2012), as demonstrated here in planarians.…”
Section: Egfr-1 Silencing Increases the Number Of Gut Progenitor Cellssupporting
confidence: 64%
“…This role in stem cell differentiation appears to be widespread among bilaterian animals (Freeman et al, 1992;Galvez-Contreras et al, 2015;Yoo et al, 2004). Moreover, studies performed in Drosophila and mouse have demonstrated the role of the EGFR pathway in the maintenance of the intestine (Jiang et al, 2011;Wong et al, 2012), as demonstrated here in planarians.…”
Section: Egfr-1 Silencing Increases the Number Of Gut Progenitor Cellssupporting
confidence: 64%
“…In the present study, we found a reduction in the expression of phosphorylated-IGF-1R in the animals that were sacrificed immediately after SD. These changes could be attributed to fluctuation in glucocorticoid levels that has been reported in SD animals ( Galvez-Contreras et al, 2016 ). IGF-1 has a rapid mechanism of action and a short biological half-life ( Rabinovsky et al, 2003 ).…”
Section: Discussionmentioning
confidence: 65%
“…Four animals per group were decapitated and hippocampi were treated with protease tablets (complete mini EDTA-free, Roche, 04693159001) plus lysis buffer (Base Tris pH = 7.5, NaCl, NaF, Na 3 VO 4 , NP40) as described previously ( Krishack et al, 2015 ; Shiwa et al, 2015 ; Galvez-Contreras et al, 2016 ). Briefly, the homogenate was centrifuged for 30 min at 14,000 rpm/4°C, and the supernatant was recovered and processed for Lowry protein assay ( Lowry et al, 1951 ).…”
Section: Methodsmentioning
confidence: 99%
“…It also expanded the number of Olig2 + cells around the lateral ventricles. Although PHT significantly decreased the proportion of mature neurons (NG2 + glia and NeuN + cells) but promoted the percent of mature oligodendrocyte RIP + cells in the OB [ 54 ]. The same investigators also showed that PHT (10 mg/kg, 30 days) dose-dependently promoted the proliferation of NSC in the SVZ and SGZ areas of the adult mice brain [ 55 ].…”
Section: The First-generation Asm and Neurogenesismentioning
confidence: 99%